(untitled) (Third Sector Social Economic Review, 2021)
Due to the dynamic structure of the healthcare sector, with the rapid developments and changes in this field, health care buyers can access information more easily and the power to manage their own health services increases as a result of the information they reach. At this point, health literacy is becoming increasingly important in order to ensure correct management and prevent negative effects on human health. It is seen that the concept of e-health literacy emerged with digitalization and increasing internet use. Considering that health is more prominent in social life in an age that is increasingly digitalized, especially during the pandemic period; At this point, the reflection of the practices of individuals as a result of e-health literacy to the society as well as themselves will be more effective. The aim of this study is to examine e-health literacy according to internet usage and demographic characteristics. In line with this purpose, individuals’ levels of finding the internet important and effective in acquiring health information, as well as the level of e-health literacy were measured and their differences with each other and their demographic characteristics were examined. Research data were collected by online survey method from individuals over the age of 18 in Ankara in September 2020. According to the results of the study, it is seen that the e-health literacy level is slightly above the average with 3,420804. In addition, by revealing the differences in the study, recommendations are made to the public, experts and health institutions.